A note on the expectations hypothesis at the founding of the Fed - Kool, Clemens J.M.; Thornton, Daniel L. (Journal of Banking & Finance, 2004)
One of the most influential tests of the expectations hypothesis is Mankiw and Miron [Q. J. Econ. 101 (1986) 211], who found that the spread between the long-term and short-term rates provided predictive power for the short-term rate before the Fed's founding but not after. They suggested that the failure of the expectations hypothesis after the Fed's founding was due to the Fed's practice of smoothing short-term interest rates. We show that their finding that the expectations hypothesis fares better prior to the Fed's founding is due to the fact that the test they employ tends to generate results that are more favorable to the expectations hypothesis during periods when there is extreme volatility in the short-term rate.